Autobiograficzne poradniki i poradnikowe teksty autobiograficzne — o „zmąconych” wariantach „niebinarnej” prozy non-fiction - Iwanicka, Julia (Zagadnienia Rodzajów Literackich, 2024)
The aim of this article is to present a variant of nonbinary non-fiction prose and the genological matter related to it. Recently, the topic of nonbinary gender identities has become increasingly popular, and more and more cultural texts devoted to it are being published. Despite this, Polish literary studies lack a deeper theoretical reflection on these issues. Perhaps this is due to the sparse representation of non-fiction books devoted to non-binarity on the Polish publishing market and the rather recent emergence of this topic in wider social debates. For this reason, the subject of analysis will be mostly contemporary books written in English — self-help guidebooks and autobiographical prose. In these pieces one notices a mix of conventions of genology. Guidebooks contain autobiographical elements, while autobiographical prose feature elements similar to guides (for example advice is given, phrases are addressed to the reader) and are treated as such by the audience. This may be related to the socially engaged character of these texts (aimed at improving the situation of nonbinary people in society), which combine collective elements with experiences of individuals. Referring to, among others, the works of Eve Kosofsky-Sedgwick, Katarzyna Trzeciak, Stanisław Balbus and Romuald Cudak, the article seeks to show the relationship between the “blurring” of these texts and their queer, community-oriented nature.